COVID-19 and endodontic emergencies (Research, Society and Development, 2021)
Clinical and epidemiological studies suggest that the transmission of COVID-19 between humans may occur through direct or indirect contact, through virus-laden respiratory droplets, from symptomatic, asymptomatic or pre-symptomatic infected people, after coughing or sneezing. Therefore, this study aimed to review in the scientific literature, effective endodontic emergency and urgency protocols applicable during the COVID-19 pandemic. Electronic searches were carried out on governmental websites, manuals and national protocols regarding guidelines related to the adaptations of emergency dental cares (endodontics) indicated during COVID-19 pandemic. The endodontic care emergencies during were considered an essential service for public health and should be performed in the best possible way, in the shortest possible time, reducing the risks of staff and patient contamination during the procedures; the protocol will depend on the patient's health condition, the type of urgency, and the dentist's skill and dexterity. Scientific evidence has shown that asymptomatic individuals can indeed spread the SARS-CoV-2 virus efficiently and, therefore, every patient should be considered potentially infected. In addition, healthcare professionals must keep up-to-date on this disease and provide their staff with adequate training.